Prevalence of Thyroid Dysfunction in Women with Dysfunctional Uterine Bleeding in Kano, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Thyroid hormones play a key role in the menstrual and reproductive functions of women. Thyroid dysfunction is marked by a large number of menstrual aberrations.Objective:To determine the incidence of thyroid dysfunction in dysfunctional uterine bleeding (DUB) and its correlation with menstrual patterns.Materials and Methods:The study population consisted of 64 DUB patients aged between 19 and 45 years and an equal number of age-matched women with a normal menstrual cycle. Plasma concentrations of thyroid-stimulating hormone (TSH), free thyroxine (T4), and free triiodothyronine (T3) of the participants were measured. Laboratory analyses were conducted on Elecsys 2010 immunology analyzer. Statistical analysis was performed with Microsoft Excel software, and the data were transferred into IBM SPSS version 21.0 for processing. AP-value of